BMDREDD REGULATES THE APOPTOSIS COORDINATING WITH BMDAXX, BMCIDE‐B, BMFADD, AND BMCREB IN BMN CELLS. Issue 3 (25th August 2016) - Chen, Rui‐ting; Jiao, Peng; Lu, Yan; Xin, Hu‐hu; Zhang, Deng‐pan; Wang, Mei‐xian; Liang, Shuang; Miao, Yun‐gen
Abstract : The apoptosis mechanisms in mammals were investigated relatively clearly. However, little is known about how apoptosis is achieved at a molecular level in silkworm cells. We cloned a caspase homologous gene named BmDredd (where Bm is Bombyx mori and Dredd is death‐related ced‐3/Nedd2‐like caspase) in Bm N cells from the ovary of Bm and analyzed its biological information. We constructed the N‐terminal, C‐terminal, and overexpression vector of BmDredd, respectively. Our results showed that the transcriptional expression level of BmDredd was increased in the apoptotic Bm N cells. Furthermore, overexpression of BmDredd increased the caspase‐3/7 activity. Simultaneously, RNAi of BmDredd could save Bm N cells from apoptosis. The immunofluorescence study showed that Bm Dredd located at the cytoplasm in normal cell otherwise is found at the nucleus when cells undergo apoptosis. Moreover, we quantified the transcriptional expressions of apoptosis‐related genes including BmDredd, BmDaxx (where Daxx is death‐domain associated protein), BmCide‐b (where Cide‐b is cell death inducing DFF45‐like effector), BmFadd (Fadd is fas‐associated via death domain), and BmCreb (where Creb is cAMP‐response element binding protein) in Bm N cells with dsRNA interferences to detect the molecular mechanism of apoptosis. In conclusion, BmDredd may function for promoting apoptosis and there are various regulatory interactions among these apoptosis‐related genes.